Reconstructing the Nakayama proposal 1991: ASEAN's objections and Japan's behind-the scenes diplomacy - Afiatanti, Dhini (2014)
The content of this paper is focused on the Nakayama Proposal 1991, an initiative of multilateral security dialogue following the end of the Cold War in 1990.The proposal was submitted by Japan’s Former Foreign Minister Tarou Nakayama towards the Association of Southeast Asian Nation (ASEAN)on July 22, 1991.Prior to 1990,in legitimate consideration of Article 9 of Japan’s Constitution and The Yoshida Doctrine, Japan’s policies towards ASEAN were limited only upon commercial field likewise economic trade as well as cultural exchange.However, Japan altered its foreign policy in 1990s and started to consider an initiative of multilateral security dialogue. One of them was the Nakayama Proposal 1991.It is said that the Nakayama Proposal 1991 was a notable initial phase related to the establishment of the ASEAN Regional Forum (ARF), one of the instruments of security-community in the Asia Pacific region.Nevertheless, there were several constraints facing this initiative, including objections to Nakayama’s idea of the Senior Officials’ Meeting (SOM) by Indonesian and Malaysian Foreign Minister, Alatas and Abdullah.Thus, this paper tries to resconstruct Japan’s behind-the-scenes worksin advance of the submission of the Nakayama Proposal by Japan’s Prime Minister and Ministry of Foreign Affairs (MoFA) officials in order to explore the reason behind ASEAN’s negative respond employing Deutsch’s concept of actors’ mobility and transactions multiplicity.By analyzing Japan and ASEAN countries’ balance of transactions through 1990 to 1991, it is remarked that the lack of direct consultation regarding the SOM concept prior to the proposal’s submission was the reason behind ASEAN’s refusal.